In Vivo Time-gated Fluorescence Imaging with Biodegradable Luminescent Porous Silicon Nanoparticles - Gu, Luo (2013)
Fluorescence imaging is one of the most versatile and widely used visualization methods in biomedical research. However, tissue autofluorescence is a major obstacle confounding interpretation of in vivo fluorescence images. The unusually long emission lifetime (5-13 μs) of photoluminescent porous silicon nanoparticles can allow the time-gated imaging of tissues in vivo, completely eliminating shorter-lived (< 10 ns) emission signals from organic chromophores or tissue autofluorescence.Here, using a conventional animal imaging system not optimized for such long-lived excited states, we demonstrate improvement of signal to background contrast ratio by > 50-fold in vitro and by > 20-fold in vivo when imaging porous silicon nanoparticles. Time-gated imaging of porous silicon nanoparticles accumulated in a human ovarian cancer xenograft following intravenous injection is demonstrated in a live mouse. The potential for multiplexing of images in the time domain by using separate porous silicon nanoparticles engineered with different excited state lifetimes is discussed.